Brazilian Research Consortium on Obsessive-Compulsive Spectrum Disorders guidelines for the treatment of adult obsessive-compulsive disorder. Part II: cognitive-behavioral therapy - de Mathis, Maria Alice; Chacon, Priscila; Boavista, Rodrigo; de Oliveira, Marcos Vinícius Sousa; de Barros, Pedro Macul Ferreira; Echevarria, Marco Antonio Nocito; Ferrão, Ygor Arzeno; Vattimo, Edoardo Filippo de Queiroz; Lopes, Antônio Carlos; Torres, Albina Rodrigues [UNESP]; Diniz, Juliana Belo; Fontenelle, Leonardo; et al. (EDITORA SCIENTIFIC, 2023)
Objectives: To summarize evidence-based cognitive-behavioral therapy (CBT) treatment and propose clinical interventions for adult patients with obsessive-compulsive disorder (OCD). Methods: The literature on CBT interventions for adult OCD, including BT and exposure and response prevention, was systematically reviewed to develop updated clinical guidelines for clinicians, providing comprehensive details about the necessary procedures for the CBT protocol. We searched the literature from 2013-2020 in five databases (PubMed, Cochrane, Embase, PsycINFO, and Lilacs) regarding study design, primary outcome measures, publication type, and language. Selected articles were assessed for quality with validated tools. Treatment recommendations were classified according to levels of evidence developed by the American College of Cardiology and the American Heart Association. Results: We examined 44 new studies used to update the 2013 American Psychiatric Association guidelines. High-quality evidence supports CBT with exposure and response prevention techniques as a first-line treatment for OCD. Protocols for Internet-delivered CBT have also proven efficacious for adults with OCD. Conclusion: High-quality scientific evidence supports the use of CBT with exposure and response prevention to treat adults with OCD.
Keywords: cognitive-behavioral therapy; exposure and response prevention; Obsessive-compulsive disorder; practice guideline; systematic review